Domestic demand drives German economy - Ferdinand Fichtner; Guido Baldi; Franziska Bremus; Karl Brenke; Christian Dreger; Hella Engerer; Christoph Große Steffen; Simon Junker; Claus Michelsen; Katharina Pijnenburg; Maximilian Podstawski; Malte Rieth; et al. (DIW Economic Bulletin, 2015)
The German economy is expected to grow by 1.7 percent this year, and to maintain this pace in 2016 as well. The rate of growth should slow down slightly (to 1.5 percent) in 2017, but only because the number of working days will be lower due to the timing of public holidays. The global economy is growing at a slower pace than it has been in recent years, but will pick up speed during the forecast period. The recessions in Russia and Brazil are coming to an end, China is orienting its economy toward more consumption-so far, without any major disruptions-and growth in the U.S. and the UK remains strong. The euro area is on the path to recovery, albeit at a moderate pace: Job creation, while modest, and an increase in real income are spurring demand in many countries. The global economy's average annual growth rate is expected to rise from 3.4 percent this year to 3.6 next year, and to 3.9 percent in the following year. In Germany, strong private consumption is the primary growth driver. The main reason for this is the ongoing pattern of strong growth of the wage bill. In the coming year, this year's positive effect of lower oil prices on households' purchasing power will fall away-yet positive impulses will also arise as a result of the refugee influx. This is connected with the care, accommodation, and integration of refugees and with the consumption this creates, as well as with increased activity in the construction industry. In contrast, investment in equipment will develop only modestly. In addition to the overall slightly weaker global sales prospects, there are also domestic factors with dampening effects. Despite robust exports, foreign trade will not contribute to growth in net terms since the dynamic domestic economy is spurring imports more powerfully.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook